치핵절제술시 사용한 Ketorolac의 제통효과 - 정상호; Sang Ho Jeong; 최인철; In Cheol Choi; 김영생; Young Saeng Kim; 송남원; Nam Won Song (Korean journal of anesthesiology, 1999)
Background : Moderate to severe postoperative pain is still treated with an intermittent intramuscular injection of narcotics. Recently introduced ketorolac is a nonsteroidal anti-inflammatory drug that has analgesic property comparable to morphine and does not increase opioid-associated side effects such as respiratory depression, nausea and vomiting. We evaluate the analgesic effect of ketorolac directly injected around the anal sphincter muscle during a hemorrhoidectomy. Methods : Forty adult patients undergoing hemorrhoidectomy were randomly assigned to one of two groups. Both groups received the operation under saddle block and by one surgeon. We administered 60 mg of ketorolac to one group (ketorolac group, n = 20) and the other group (control group, n = 20) received no pain medication intraoperatively. Postoperative visual analogue pain scores (VAS), analgesic requirements and side effects were examined and compared between two groups. Results : VAS at 6 hours after surgery were significantly less (P＜ 0.05) in the ketorolac group (3.1±1.5) than in the control group (6.0±1.2) and demerol consumption during the first 6 hours after surgery in the ketorolac group was significantly less (P＜ 0.05) than in the control group (35 mg vs 62.5 mg). The ketorolac group also showed significantly less incidence of urinary retention than the control group (P ＜ 0.05). Conclusions : 60 mg of ketorolac administered during hemorrhoidectomy was partially effective for postoperative pain control and the incidence of urinary retention was significantly reduced. (Korean J Anesthesiol 1999; 37: 819∼824)